2020
DOI: 10.31289/analitika.v12i1.2815
|View full text |Cite
|
Sign up to set email alerts
|

Kontribusi Identitas Budaya Jawa yang Dimediasi oleh Cognitive Reappraisal dalam Membentuk Resiliensi Keluarga pada Keluarga Suku Jawa

Abstract: Penelitian ini mencoba menggali faktor protektif resiliensi keluarga dari hal yang paling dekat dengan kehidupan individu, yaitu budaya. Penelitian ini bertujuan untuk melihat apakah identitas budaya Jawa berkontribusi pada internalisasi cognitive reappraisal dalam membentuk resiliensi keluarga pada keluarga suku Jawa. Responden penelitian terdiri dari 317 orang tua, bersuku Jawa, laki-laki (35%) dan perempuan (65%), berusia 25-63 tahun (M= 44, SD=7.1) yang diperoleh melalui tehnik convenience sampling. Pengam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Remaja yang memiliki kebermaknaan hidup, remaja tersebut akan mampu mengambil hikmah positif dari setiap kejadian yang terjadi dalam hidupnya, remaja dapat menghargai dirinya sendiri, sehingga mereka dapat bangkit dan mengatasi setiap permasalahan yang menimpanya. Remaja yang dapat bangkit dan mengatasi permasalahan artinya remaja tersebut sudah memiliki resiliensi (Azizah, & Pudjiati, 2020;Rachmawati et al, 2019).…”
Section: Pendahuluanunclassified
“…Remaja yang memiliki kebermaknaan hidup, remaja tersebut akan mampu mengambil hikmah positif dari setiap kejadian yang terjadi dalam hidupnya, remaja dapat menghargai dirinya sendiri, sehingga mereka dapat bangkit dan mengatasi setiap permasalahan yang menimpanya. Remaja yang dapat bangkit dan mengatasi permasalahan artinya remaja tersebut sudah memiliki resiliensi (Azizah, & Pudjiati, 2020;Rachmawati et al, 2019).…”
Section: Pendahuluanunclassified
“…A previous study on the family resilience of Batak Toba families showed that family strain and coping contributed directly to family resilience, meanwhile community support mediated the contribution of cultural identity and socioeconomic status (Pudjiati, 2016). A study about family resilience of Javanese families examined the mediating role of cognitive appraisal of the relationship between cultural identity and family resilience (Azizah & Pudjiati, 2020). Results of the study showed that the mediating role of cognitive appraisal was not significant, indicating that cultural identity contributed directly to family resilience in Javanese families.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there was a phenomenon in Minangkabau people in West Sumatera, that was the increasing rate of divorce for the last three years by 59.1% from 2017 to 2019 (Badan Pusat Statistik Povinsi Sumatera Barat, 2020). The increase in the divorce rate indicates the declining ability of families to manage and maintain family functioning (Azizah & Pudjiati, 2020), therefore the process and factors of Minangkabau people's family resilience need further exploration. There were some causes of divorces in West Sumatera, those three dominant causes were no commitment between spouses, no compatibility to each other, and third-party interference.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Yusoff et al, (2019) revealed that there is a significant relationship between resilience and cognitive distortions. Azizah and Pudjiati (2020) suggest that cognitive assessment contributes to shaping family resilience. Viewed from the dynamic systems framework, the family is a system, where the conditions or challenges faced by family members will have an impact on the family system.…”
Section: Introductionmentioning
confidence: 99%